Small Molecule Inhibition of CPS1 Activity through an Allosteric Pocket. Issue 3 (19th March 2020) - Yao, Shihua; Nguyen, Tuong-Vi; Rolfe, Alan; Agrawal, Anant A.; Ke, Jiyuan; Peng, Shouyong; Colombo, Federico; Yu, Sean; Bouchard, Patricia; Wu, Jiayi; Huang, Kuan-Chun; Bao, Xingfeng; et al.
Summary: Carbamoyl phosphate synthetase 1 (CPS1) catalyzes the first step in the ammonia-detoxifying urea cycle, converting ammonia to carbamoyl phosphate under physiologic conditions. In cancer, CPS1 overexpression supports pyrimidine synthesis to promote tumor growth in some cancer types, while in others CPS1 activity prevents the buildup of toxic levels of intratumoral ammonia to allow for sustained tumor growth. Targeted CPS1 inhibitors may, therefore, provide a therapeutic benefit for cancer patients with tumors overexpressing CPS1. Herein, we describe the discovery of small-molecule CPS1 inhibitors that bind to a previously unknown allosteric pocket to block ATP hydrolysis in the first step of carbamoyl phosphate synthesis. CPS1 inhibitors are active in cellular assays, blocking both urea synthesis and CPS1 support of the pyrimidine biosynthetic pathway, while having no activity against CPS2. These newly discovered CPS1 inhibitors are a first step toward providing researchers with valuable tools for probing CPS1 cancer biology. Graphical Abstract: Highlights: A high-throughput screen identifies a small-molecule inhibitor of CPS1, H3B-120 H3B-120 binds to an allosteric pocket to achieve highly selective inhibition of CPS1 Analogs of H3B-120 block CPS1 cellular activity in primary human hepatocytes Abstract : CPS1 is a proposed oncoprotein of interest for drug development. Yao et al. describe the discovery of small-molecule inhibitors of CPS1 and discuss their proposed impact for studying CPS1 cancer biology.